The European health data space: Too big to succeed? - Marelli, Luca; Stevens, Marthe; Sharon, Tamar; Van Hoyweghen, Ine; Boeckhout, Martin; Colussi, Ilaria; Degelsegger-Márquez, Alexander; El-Sayed, Seliem; Hoeyer, Klaus; van Kessel, Robin; Zając, Dorota Krekora; Matei, Mihaela; et al. (Health policy (Amsterdam), 2023)
•In the current Proposal, the EHDS will not achieve its stated aims.•The EHDS will entail diminished safeguards for patients and citizens.•Health professionals are assigned unsustainable administrative burdens, detracting from patient care.•Current data governance practice may insufficiently translate to value for the public.•The proposal should be amended towards strengthening individual control and promoting collective good. In May 2022, the European Commission issued the Proposal for a Regulation on the European Health Data Space (EHDS), with the aims of granting citizens increased access to and control of their (electronic) health data across the EU, and facilitating health data re-use for research, innovation, and policymaking. As the first in a series of European domain-specific “data spaces”, the EHDS is a high-stakes development that will transform health data governance in the EU region. As an international consortium of experts from health policy, law, ethics and the social sciences, we are concerned that the EHDS Proposal will detract from, rather than lead to the achievement of, its stated aims. We are in no doubt on the benefits of using health data for secondary purposes, and we appreciate attempts to facilitate such uses across borders in a carefully curated manner. Based on the current draft Regulation, however, the EHDS risks undermining rather than enhancing patient control over data; hindering rather than facilitating the work of health professionals and researchers; and eroding rather than increasing the public value generated through health data sharing. Therefore, significant adjustments are needed if the EHDS is to realize its promised benefits. Besides analyzing the implications for key groups and European societies at large who will be affected by the implementation of the EHDS, this contribution advances targeted policy recommendations to address the identified shortcomings of the EHDS Proposal.